The effect of percutaneous nephrolithotomy in patients with chronic kidney disease in northeast India population - Deka, Phanindra Mohan; Rajput, Manharsinh; Sarma, Priyanku Pratik (International Surgery Journal, 2021)
Background: Renal stone disease is a recognized precursor for renal deterioration, if untreated, it can lead to renal failure. With advances in the PCNL technique, it's effect on patients with established renal insufficiency remains under reported. So, we aimed to evaluate the efficacy as well as safety of PCNL in chronic kidney disease patients. Methods: This retrospective cohort study included patients admitted to our hospital from January 2016 to December 2018, which were diagnosed with urolithiasis and chronic kidney disease and treated by PCNL. Patients with GFR <60 ml/min/1.73 m2 in the non-obstructed renal stone disease who underwent PCNL were included. We studied the change in renal function, complete stone free rate (SFR), complications, stone composition, operative time and hospital stay. Results: The study comprised 50 patients (M/F-32/18) Of CKD who underwent PCNL. Mean operative time was 90.50±12.57minutes in group 1 and 98.00±12.35 minutes in group 2. One or more complications were noted in 12 patients (24%) after PCNL. At a mean follow-up of 18 months, renal function stage had improved in 24 patients (48%) and it was maintained in 13 (26%). Worsening of CKD with an increase in disease stage was noted in 13 patients (26%). Association between hypertension, diabetes, and postoperative deterioration in kidney function wasn’t significant statistically (p=0.9). The stone-free rate at postoperative month 3 was 76%. Conclusions: PCNL has a favourable outcome in patients with chronic kidney disease stage III/IV, with a good calculus clearance rate and improved kidney function.